Active tuberculosis in household contacts of bacteriologically confirmed pulmonary tuberculosis patients: A multicenter study finding the 'Missed One' in Central Ethiopia. - Getachew Seid; Ayinalem Alemu; Getu Diriba; Michael Hailu; Amanuel Wondimu; Mengistu Tadesse; Gemechu Tadesse; Solomon H Mariam; Balako Gumi (PLoS ONE)
Background There was a 'missing millions' gap between the incidence of tuberculosis (TB) cases and the notified cases. In many TB high-burden countries, only about 25% of household contacts (HHCs) completing household TB evaluation and 20-89% of eligible contacts did not adhere to TB screening. The study was conducted to assess the yield of door-to-door TB household contact investigation among household contact of bacteriologically confirmed pulmonary TB cases in central Ethiopia. Methods This cross-sectional study was carried out in selected health facilities of central Ethiopia from January 1, 2023 to December 3, 2023.All sequential voluntary bacteriologically confirmed TB patients and their HHCs without discrimination by age were included in the study. Xpert Ultra assay and TB culture were used to investigate active TB from sputum sample. Spearman's correlation analysis was used to determine the correlation between the index case cycle threshold value and the corresponding HHCs. Multivariable logistic regression analysis was done to investigate the associated risk factors for active TB in HHCs. Results Among 967 HHCs claimed by 303 index cases (259 drug susceptible TB (DS-TB) and 44 multi-drug resistance TB (MDR/RR-TB)), 902(93.07%) HHCs had received baseline symptom-based TB evaluation. Presumptive TB was identified in 20.17% (182) of the evaluated HHCs and 13(1.44%) were diagnosed with active TB. Eleven HHCs (7.24%; 95% CI: 3.85-12.9%) from DS-TB index case contacts and 2 (6.67%; 95% CI: 1.16-23.51) from MDR/RR-TB indexes HHCs were found to be MTB detected Rifampicin resistance not detected cases. The Xpert ultra assay results revealed an 84.62% (95% CI: 57.77-95.68) Rifampicin drug resistance concordance between the index case and the corresponding HHC. Active TB was significantly associated with night sweating and sharing a bed with the index patient, P-value < 0.05. Conclusion Home-to-home TB contact screening have high active TB yield and implementable in both rural and urban areas of the nation only by mentoring and motivating the health extension workers. Proximity to bacteriologically confirmed TB patient for long time exposes household contacts for active TB. Scheduling convenient times and last-mile service delivery to contacts is very important to address the missed active TB cases in the community.